Engineering recombinantly expressed lectin-based antiviral agents - Maier, Irene (Frontiers in Cellular and Infection Microbiology, 2022)
Cyanovirin-N (CV-N), a lectin from Nostoc ellipsosporum was found an infusion inhibitory protein for human immunodeficiency virus (HIV)-1. A tandem-repeat of the engineered domain-swapped dimer bound specific sites at hemagglutinin (HA), Ebola and HIV spike glycoproteins as well as dimannosylated HA peptide, N-acetyl-D-glucosamine and high-mannose containing oligosaccharides. Among these, CV-N bound the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) spike protein at a dissociation constant (KD) of 18.6 µM (and KD=260 µM to RBD), which was low-affinity carbohydrate-binding as compared with the recognition of the other viral spikes. Binding of dimannosylated peptide to homo-dimeric CVN2 and variants of CVN2 that were pairing Glu-Arg residues sterically located close to its high-affinity carbohydrate binding sites, was measured using surface plasmon resonance (SPR) and isothermal titration calorimetry (ITC). Binding affinity increased with polar interactions, when the mutated residues were used to substitute a single, or two disulfide bonds, in CVN2. Site-specific N-linked glycans on spikes were mediating the infection with influenza virus by broadly neutralizing antibodies to HA and lectin binding to HA was further investigated via modes of saturation transfer difference (STD)-NMR. Our findings showed that stoichiometry and the lectin’s binding affinity were revealed by an interaction of CVN2 with dimannose units by either the high- or low-affinity binding site. To understand how these binding mechanisms add to viral membrane fusion we compare our tested HA-derived peptides in affinity with SARS-CoV-2 glycoprotein and review lectins and their mechanisms of binding to enveloped viruses for a potential use to simulate neutralization ability.